Response of xylem parenchyma by suberization in some hardwoods after mechanical injury (Trees, 1993)
Wound responses of xylem parenchyma by suberizarion were investigated in some hardwoods by light and electron microscopy. Suberized ray and axial paren- chyma cells form a distinct boundary around the wound in all investigated species. Vessels and fibres within and close behind the suberized area appeared more or less occluded; vessels in Fagus, Quercus, and Populus contained suber- ized tyloses, those in Betula and Tilia contained amor- phous and fibrillar deposits. A common mechanism for suberin deposition in the parenchyma cells became evi- dent. Cisternae of the endoplasmic reticulum were ap- parently involved in suberization. Suberin compounds are extruded by cytoplasmic vesicles, which fused with the plasma membrane, in order to release their content. The suberin layer exhibited the typical lamellated structure; cytoplasmic continuity between suberized cells by plas- modesmata was maintained through the suberin layer. Fagus revealed the most intense suberized area as com- pared with the other species. Within the reaction zone of Fagus and Quercus, some individual ray and axial paren- chyma cells exhibited a subdivision into 2 or 3 compart- ments prior to suberization. Subdivision was achieved by the formation of a primary wall-like layer. Subsequently, the compartments became individually suberized. Wound- ing during winter did not induce suberization. Also, samples wounded and kept under water during the vegeta- tion period showed no response. The role of suberization in the effectivity of wound-associated compartmentalization is discussed.